Effective Medicinal Plant in Cancer Treatment, Part 2: Review Study - Wesam Kooti MSC; Karo Servatyari MD; Masoud Behzadifar PhD; Majid Asadi-Samani PhD; Fatemeh Sadeghi MSc; Bijan Nouri PhD; Hadi Zare Marzouni MSc (SAGE Publishing, 2017)
Cancer is the second cause of death after cardiovascular diseases. With due attention to rapid progress in the phytochemical study of plants, they are becoming popular because of their anticancer effects. The aim of this study was to investigate the effective medicinal plants in the treatment of cancer and study their mechanism of action. In order to gather information the keywords "traditional medicine," "plant compounds," "medicinal plant," "medicinal herb," "toxicity," "anticancer effect," "cell line," and "treatment" were searched in international databases such as ScienceDirect, PubMed, and Scopus and national databases such as Magiran, Sid, and Iranmedex, and a total of 228 articles were collected. In this phase, 49 nonrelevant articles were excluded. Enhancement P53 protein expression, reducing the expression of proteins P27, P21, NFκB expression and induction of apoptosis, inhibition of the PI3K/Akt pathway, and reduction of the level of acid phosphatase and lipid peroxidation are the most effective mechanisms of herbal plants that can inhibit cell cycle and proliferation. Common treatments such as radiotherapy and chemotherapy can cause some complications. According to results of this study, herbal extracts have antioxidant compounds that can induce apoptosis and inhibit cell proliferation by the investigated mechanisms.